Market Segmentation of Carica Products in Wonosobo Regency (Case Study on Telaga Warna Tourism Object and Sikunir Village Tourism Area) - Syafiq, Muhammad; Siti Rahayu, Endang; Sutrisno, Joko (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Agribusiness is defined as business in agricultural sector that uses natural potential of Indonesia as the main commodity, hence it is possibly conducted in every region in Indonesia. Each region has its own advantages that represents the area characteristics, progressing into a leading commodity and further as an icon of a region. Wonosobo Regency is one of regions characterized by carica products that can only grow and develop in Dieng Plateau. This study aimed at investigating the market segmentation of carica product. The descriptive method was applied using 96 samples of respondents for data collection through questionnaire. Respondents were collected from two tourism areas in Wonosobo Regency, namely Telaga Warna and Sikunir. The results showed that the respondent’s age and monthly expense variables significantly and positively affected the Carica product purchase in both tourism objects.